Preparation method of ultra-high-rate and high-energy-density water system supercapacitor

By using small-size graphene and Ti3C2Tx two-dimensional nanosheets to construct asymmetric supercapacitor devices, the problem of insufficient energy density at ultra-high magnification in the existing technology is solved, and a water-based supercapacitor with high voltage and high energy density is realized, which satisfies the energy The demand for outbreak scenarios.

CN119314811AActive Publication Date: 2025-01-14SHANGHAI JIAOTONG UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411707911.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-01-14
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

Existing supercapacitors are difficult to achieve high energy density at ultra-high magnifications, and the manufacturing and service environment of organic supercapacitors is demanding, and the electrochemical stability window of water-based supercapacitors is narrow, making it difficult to meet the practical application needs.

Method used

Small-size graphene and Ti3C2Tx two-dimensional nanosheets are used as electrode materials, and small-size two-dimensional nanosheets are prepared by probe ultrasonic and centrifugal purification to build asymmetric supercapacitor devices, using high-conductivity sulfuric acid electrolyte and positive and negative electrode materials Match, adjust the open circuit potential for high voltage and high energy density.

Benefits of technology

It significantly improves the charging and discharging capacity of ultra-high rate, and realizes the high voltage and high energy density of water-based supercapacitors, with a voltage up to 1.8V, and the energy density is maintained well at ultra-high rate, with a capacitance retention rate greater than 95%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119314811A_ABST
    Figure CN119314811A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an ultrahigh-rate and high-energy-density water system supercapacitor, and relates to the technical field of supercapacitors, and the method comprises the following steps: 1, preparing a small-size graphene two-dimensional nanosheet; step 2, preparing a small-size Ti < 3 > C < 2 > T < x > two-dimensional nanosheet; 3, a small-size graphene two-dimensional nanosheet hydration film and a small-size Ti < 3 > C < 2 > T < x > two-dimensional nanosheet hydration film are prepared, the small-size graphene two-dimensional nanosheet hydration film serves as a positive electrode, and the small-size Ti < 3 > C < 2 > T < x > two-dimensional nanosheet hydration film serves as a negative electrode; and step 4, separating the small-size graphene two-dimensional nanosheet hydrated thin film from the small-size Ti3C2Tx two-dimensional nanosheet hydrated thin film by using a diaphragm, and then injecting an electrolyte to realize the assembly of the water system supercapacitor. According to the invention, a small-size two-dimensional nanosheet is used as an electrode material, and the obtained supercapacitor can show high energy density under ultrahigh rate by selecting positive and negative electrode materials, adjusting positive and negative electrode open-circuit potentials and matching positive and negative electrode capacities and masses.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of supercapacitors, and in particular to a method for preparing an ultra-high rate, high energy density aqueous supercapacitor. Background Art

[0002] Supercapacitors are one of the most important electrochemical energy storage devices, with high power density and long cycle life. They can meet the needs of short-term and frequent charging and discharging application scenarios (such as grid peak shaving and valley flattening, braking energy regeneration, etc.), and are an effective supplement to metal ion batteries (high energy density, low power density). Currently, supercapacitors in commercial applications are mainly organic supercapacitors based on activated carbon electrodes, which can achieve charging and discharging in tens of seconds to minutes, but it is difficult to achieve ultra-high rate (charging and discharging within 3.6s, greater than 1,000C) energy storage and release, and cannot meet the needs of energy burst scenarios. In addition, the manufacturing and service environment of organic supercapacitors are demanding, requiring strict control of moisture and strict sealing during the preparation process, and the organic solvents in their electrolytes are volatile, flammable, explosive, toxic and costly.

[0003] Aqueous electrolytes have smaller cation sizes and higher ionic conductivity (up to 1.0S / cm), so using them as supercapacitor electrolytes can achieve faster charging and discharging speeds and higher capacitance, making it more likely to achieve ultrafast supercapacitors. In addition, aqueous electrolytes are green, non-toxic, safe, and low-cost, making them more suitable for practical applications than organic electrolytes. However, aqueous supercapacitor devices are limited by the narrow electrochemical stability window (1.23V) of aqueous electrolytes, making it difficult to achieve high voltage and high energy density, and difficult to meet the needs of practical applications.

[0004] Two-dimensional nanosheet materials have high electronic and ionic conductivity and high theoretical specific surface area, making them ideal supercapacitor electrode materials. To achieve ultra-high rate supercapacitors, it is necessary to carefully design the ion transmission channels inside the electrode so that the electrode with a high surface loading of active substances can achieve ultra-high rate charge and discharge. Existing research has mainly focused on electrodes based on two-dimensional nanosheets with micron-sized lateral dimensions, but their internal ion transmission channels are lengthy, making it difficult to achieve ultra-high rate charge and discharge. The use of small-sized two-dimensional nanosheets can significantly reduce the lateral ion transmission distance and increase the number of vertical ion transmission channels, thereby significantly improving its ultra-high rate charge and discharge capabilities. In addition, by matching the positive and negative electrode materials, the construction of asymmetric supercapacitor devices can make full use of their stable voltage window to achieve high voltage and high energy density.

[0005] At present, the research on the preparation of ultra-high rate (greater than 1,000C) supercapacitors is still limited by the extremely low energy density and cannot meet the needs of practical applications. Solving this problem has important theoretical and practical significance.

[0006] Therefore, technicians in this field are committed to developing a method for preparing an ultra-high rate, high energy density aqueous supercapacitor that can exhibit high energy density at an ultra-high rate. Summary of the invention

[0007] In view of the above-mentioned defects of the prior art, the technical problem to be solved by the present invention is how to enable the supercapacitor to work at an ultra-high rate.

[0008] To achieve the above object, the present invention provides a method for preparing an ultra-high rate, high energy density aqueous supercapacitor, the method comprising the following steps:

[0009] Step 1, preparing small-sized graphene two-dimensional nanosheets;

[0010] Step 2: Preparation of small size Ti3C2T x Two-dimensional nanosheets;

[0011] Step 3: Preparation of small-sized graphene hydrated films and small-sized Ti3C2T x Hydration film, the small-sized graphene hydrated film is used as a positive electrode, the small-sized Ti3C2T x The hydrated film serves as the negative electrode;

[0012] Step 4: Hydration of the small-sized graphene two-dimensional nanosheet film and the small-sized Ti3C2T x The two-dimensional nanosheet hydrated thin film is separated by a diaphragm, and then an electrolyte is injected to realize the assembly of the aqueous supercapacitor.

[0013] Furthermore, the step 1 further comprises:

[0014] Step 1.1, preparing large-sized graphene two-dimensional nanosheets;

[0015] Step 1.2: Obtain small-sized graphene two-dimensional nanosheets through probe ultrasound and centrifugal purification.

[0016] Furthermore, in step 1.1, the large-sized graphene two-dimensional nanosheets are large-sized reduced oxide graphene two-dimensional nanosheets or large-sized electrochemically exfoliated graphene two-dimensional nanosheets.

[0017] Furthermore, the method for preparing the large-sized reduced graphene oxide two-dimensional nanosheets comprises: oxidizing flake graphite using the Hummer's method to obtain large-sized graphene oxide two-dimensional nanosheets, and then reducing the flake graphite to obtain large-sized reduced graphene oxide two-dimensional nanosheets;

[0018] Furthermore, the preparation method of large-size electrochemically exfoliated graphene two-dimensional nanosheets includes: using 0.1M (NH4)2SO4 aqueous solution as electrolyte, using graphite paper and platinum mesh as positive and negative electrodes respectively, and using a direct current power supply to apply a voltage of 10V to electrochemically exfoliate graphite to obtain large-size electrochemically exfoliated graphene two-dimensional nanosheets.

[0019] Furthermore, the step 2 further comprises:

[0020] Step 2.1: Preparation of large-size Ti3C2T by LiF / HCl etching x Two-dimensional nanosheets;

[0021] Step 2.2: Obtain small-sized Ti3C2T by probe ultrasonication and centrifugal purification x Two-dimensional nanosheets.

[0022] Furthermore, step 3 further comprises: using a filtration device with a diameter of 38 mm, adding 60 mg of small-sized graphene two-dimensional nanosheets or small-sized Ti3C2T x The nanosheet suspension was vacuum filtered until the liquid disappeared and then stopped immediately to obtain small-sized graphene two-dimensional nanosheet hydrated films and small-sized Ti3C2T x Two-dimensional nanosheet hydrated film, in which the nanoparticles are arranged parallel to the surface.

[0023] Furthermore, the diaphragm is a glass fiber filter membrane.

[0024] Furthermore, the electrolyte is H2SO4.

[0025] Furthermore, the open circuit potential of the positive electrode and the negative electrode is adjusted to -0.35V.

[0026] The two-dimensional nanosheet hydrated film adjusts the open circuit potentials of the positive electrode and the negative electrode to -0.35V.

[0027] Compared with the prior art, the present invention has at least the following beneficial technical effects:

[0028] 1. The present invention uses small-sized two-dimensional nanosheets as electrode materials, which significantly reduces the lateral ion transmission distance and increases the number of vertical ion transmission channels, thereby significantly improving its ultra-high rate charge and discharge capabilities; by matching the positive and negative electrode materials, constructing an asymmetric supercapacitor device can fully utilize its stable voltage window to achieve high voltage and high energy density.

[0029] 2. The present invention adopts a sulfuric acid electrolyte with high conductivity and small ion size, and uses positive and negative electrode materials with stable electrochemical voltage windows. The voltage of the obtained aqueous supercapacitor is as high as 1.8V, and it exhibits an energy density similar to that of organic capacitors at low rates.

[0030] The concept, specific structure and technical effects of the present invention will be further described below in conjunction with the accompanying drawings to fully understand the purpose, characteristics and effects of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 is a method flow chart of a preferred embodiment of the present invention;

[0032] Figure 2 It is a schematic diagram of the size statistics of a small-sized reduced graphene oxide two-dimensional nanosheet according to a preferred embodiment of the present invention;

[0033] Figure 3 It is a small-sized Ti3C2T x Schematic diagram of the size statistics of two-dimensional nanosheets;

[0034] Figure 4 This is a scanning electron microscope image of a cross section of a hydrated film of a small-sized reduced graphene oxide two-dimensional nanosheet according to a preferred embodiment of the present invention;

[0035] Figure 5 It is a small-sized Ti3C2T x SEM image of the cross section of a 2D nanosheet hydrated film;

[0036] Figure 6 Schematic diagram of the performance of a water-based supercapacitor according to a preferred embodiment of the present invention;

[0037] Figure 7 It is a performance diagram of a water-based supercapacitor according to a preferred embodiment of the present invention. DETAILED DESCRIPTION

[0038] The following describes several preferred embodiments of the present invention with reference to the drawings in the specification, so that the technical content is clearer and easier to understand. The present invention can be embodied in many different forms of embodiments, and the protection scope of the present invention is not limited to the embodiments mentioned in the text.

[0039] In the drawings, components with the same structure are indicated by the same numerical reference numerals, and components with similar structures or functions are indicated by similar numerical reference numerals. The size and thickness of each component shown in the drawings are arbitrarily shown, and the present invention does not limit the size and thickness of each component. In order to make the illustration clearer, the thickness of the components is appropriately exaggerated in some places in the drawings.

[0040] Example 1

[0041] This example is based on reduced graphene oxide and Ti3C2T x Two-dimensional nanosheets, with a positive and negative electrode surface loading of 5.0 mg / cm 2 The construction example of the aqueous supercapacitor device is shown in FIG. Figure 1 As shown, the specific steps are as follows:

[0042] Step 1: oxidize flake graphite using Hummer's method to obtain large-sized graphene oxide two-dimensional nanosheets, then hydrothermally reduce it using hydrazine hydrate and ammonia water to obtain large-sized reduced graphene oxide (large-sheets of graphene oxide, LSs-GO) two-dimensional nanosheets, and then obtain small-sized reduced graphene oxide (small-sheets of graphene oxide, SSs-GO) two-dimensional nanosheets with an average lateral size of about 94 nm by 3h of 1800W probe ultrasound and 8h of 11000rpm centrifugal purification, such as Figure 2 As shown, Figure 2 a is a scanning electron microscope image of a small-sized reduced graphene oxide two-dimensional nanosheet. Figure 2 b Distribution of lateral sizes of 2D nanosheets.

[0043] Step 2: Prepare large-size Ti3C2T by etching using LiF / HCl method x The two-dimensional nanosheets were purified by 1 h of 650 W probe ultrasound and 2 h of centrifugation at 10,000 rpm to obtain small-sized Ti3C2T with an average lateral size of about 126 nm. x Two-dimensional nanosheets, such as Figure 3 As shown, Figure 3 a is a scanning electron microscope image of a small-sized Ti3C2Tx two-dimensional nanosheet. Figure 3 b is the distribution of the lateral size of the two-dimensional nanosheets.

[0044] Step 3: Using a 38 mm diameter filtration device, add 60 mg of small-sized graphene oxide two-dimensional nanosheets or small-sized Ti3C2T x The suspension of two-dimensional nanosheets is vacuum filtered until the liquid disappears and then immediately stopped to obtain small-sized graphene oxide two-dimensional nanosheet hydrated films and small-sized Ti3C2T x Two-dimensional nanosheet hydrated film, in which nanosheets are arranged parallel to the surface, e.g. Figure 4 , Figure 5 As shown, a small-sized graphene oxide two-dimensional nanosheet hydrated film is used as the positive electrode, and a small-sized Ti3C2T x Two-dimensional nanosheet hydrated film as anode.

[0045] Step 4: Hydration of small-sized graphene oxide two-dimensional nanosheets and small-sized Ti3C2T x The two-dimensional nanosheet hydrated film is separated by a diaphragm, and then the electrolyte is injected to assemble the supercapacitor device, and the open circuit potential of the positive and negative electrodes is adjusted to about -0.35 V. Among them, the diaphragm is a layer of glass fiber filter membrane, and the electrolyte is 3 mol / L H2SO4.

[0046] The performance of the supercapacitor is verified, such as Figure 6 As shown, Figure 6 a is the cyclic voltammetry curve of the positive and negative electrodes (scan rate is 10mV / s), Figure 6 b is the constant current charge and discharge curve of the aqueous supercapacitor device at different voltages (current density is 1A / g), Figure 6 c is the real-time potential of the positive and negative electrodes during constant current charging and discharging. Figure 6 d is the cyclic voltammetry curve of the aqueous supercapacitor device at different voltages (scan rate is 10 mV / s). Figure 6 e is the mass specific energy density and coulombic efficiency of the aqueous supercapacitor device at different voltages. The test results show that the device voltage can reach 1.8V and exhibits 0.29Wh / cm at a discharge rate of about 14C. 2 The energy density is 0.14 and 0.09Wh / cm at ultra-high rates of 2000C and 3700C, respectively. 2 The energy density of the battery is 10A / g, and the capacitance retention rate is greater than 95% after 10,000 charge and discharge cycles. Figure 7 As shown, Figure 7 a is the cyclic voltammetry curve of the aqueous supercapacitor device at different scan rates. Figure 7 b is the constant current charge and discharge curve of the aqueous supercapacitor device at different current densities. Figure 7 c is the energy density and power density of the aqueous supercapacitor device, Figure 7 d is the cycling stability of the aqueous supercapacitor device.

[0047] Example 2

[0048] This example is based on electrochemical exfoliation of graphene and Ti3C2T with an average lateral size of about 100 nm. x Two-dimensional nanosheets, with a positive and negative electrode surface loading of 5.0 mg / cm 2 The specific steps are as follows:

[0049] Step 1: Use 0.1M (NH4)2SO4 aqueous solution as electrolyte, graphite paper and platinum mesh as positive and negative electrodes respectively, use a DC power supply to apply a voltage of 10V to electrochemically exfoliate graphite to obtain large-sized graphene two-dimensional nanosheets, and then obtain small-sized electrochemically exfoliated graphene two-dimensional nanosheets with an average lateral size of about 100nm through 3h of 1800W probe ultrasound and 3h of 11000rpm centrifugal purification.

[0050] Step 2: Prepare large-size Ti3C2T by etching using LiF / HCl method x The two-dimensional nanosheets were purified by 1 h of 650 W probe ultrasound and 2 h of 10,000 rpm centrifugation to obtain small-sized Ti3C2T with an average lateral size of about 100 nm. x Two-dimensional nanosheets.

[0051] Step 3: Using a 38 mm diameter filtration device, add 60 mg of small-sized electrochemically exfoliated graphene two-dimensional nanosheets or small-sized Ti3C2T x The suspension of two-dimensional nanosheets was vacuum filtered until the liquid disappeared and then immediately stopped. The active material surface loading was 5.0 mg / cm 2 Small-sized electrochemically exfoliated graphene two-dimensional nanosheet hydrated films and small-sized Ti3C2T x Two-dimensional nanosheet hydrated films serve as the positive and negative electrodes of supercapacitors.

[0052] Step 4: Electrochemically exfoliate small-sized graphene two-dimensional nanosheets and hydrated thin films of small-sized Ti3C2T x The two-dimensional nanosheet hydrated film is separated by a diaphragm, and then the electrolyte is injected to assemble the supercapacitor device, and the open circuit potential of the positive and negative electrodes is adjusted to about -0.35 V. Among them, the diaphragm is a layer of glass fiber filter membrane, and the electrolyte is 3 mol / L H2SO4.

[0053] The performance of the supercapacitor was verified, and the test results showed that the device voltage could reach 1.8V and exhibited 0.28Wh / cm at a discharge rate of about 10C. 2 The energy density of the 2000C ultra-high rate is 0.15Wh / cm 2 The energy density is 10A / g, and the capacitance retention rate is greater than 95% after 10,000 charge and discharge cycles at a current density of 10A / g.

[0054] Example 3

[0055] This example is based on electrochemical exfoliation of graphene and Ti3C2T x Two-dimensional nanosheets, with a positive and negative electrode surface loading of 5.0 mg / cm 2The specific steps are as follows:

[0056] Step 1: Use 0.1M (NH4)2SO4 aqueous solution as electrolyte, graphite paper and platinum mesh as positive and negative electrodes respectively, use a DC power supply to apply a voltage of 10V to electrochemically exfoliate graphite to obtain large-sized graphene two-dimensional nanosheets, and then obtain small-sized electrochemically exfoliated graphene two-dimensional nanosheets with an average lateral size of about 50nm through 3h of 1800W probe ultrasound and 8h of 11000rpm centrifugal purification.

[0057] Step 2: Prepare large-size Ti3C2T by etching using LiF / HCl method x The two-dimensional nanosheets were then purified by 3 h of 650 W probe ultrasound and 3 h of 10,000 rpm centrifugation to obtain small-sized Ti3C2T with an average lateral size of about 100 nm. x Two-dimensional nanosheets.

[0058] Step 3: Using a 38 mm diameter filtration device, add 60 mg of small-sized electrochemically exfoliated graphene two-dimensional nanosheets or small-sized Ti3C2T x The suspension of two-dimensional nanosheets was vacuum filtered until the liquid disappeared and then immediately stopped, and the active material surface loading was 5.0 mg / cm 2 Small-sized electrochemically exfoliated graphene two-dimensional nanosheet hydrated films and small-sized Ti3C2T x Two-dimensional nanosheet hydrated films serve as the positive and negative electrodes of supercapacitors.

[0059] Step 4: Electrochemically exfoliate small-sized graphene two-dimensional nanosheets and hydrated thin films of small-sized Ti3C2T x The two-dimensional nanosheet hydrated film is separated by a diaphragm, and then the electrolyte is injected to assemble the supercapacitor device, and the open circuit potential of the positive and negative electrodes is adjusted to about -0.35 V. Among them, the diaphragm is a layer of glass fiber filter membrane, and the electrolyte is 3 mol / L H2SO4.

[0060] The performance of the supercapacitor was verified, and the test results showed that the device voltage could reach 1.8V and exhibited 0.29Wh / cm at a discharge rate of about 10C. 2 The energy density of the 2000C ultra-high rate is 0.17Wh / cm 2 The energy density is 10A / g, and the capacitance retention rate is greater than 95% after 10,000 charge and discharge cycles at a current density of 10A / g.

[0061] Example 4

[0062] This example is based on electrochemical exfoliation of graphene and Ti3C2T with an average lateral size of about 200 nm.x Two-dimensional nanosheets, with a positive and negative electrode surface loading of 5.0 mg / cm 2 The specific steps are as follows:

[0063] Step 1: Use 0.1M (NH4)2SO4 aqueous solution as electrolyte, graphite paper and platinum mesh as positive and negative electrodes respectively, use a DC power supply to apply a voltage of 10V to electrochemically exfoliate graphite to obtain large-sized graphene two-dimensional nanosheets, and then obtain small-sized electrochemically exfoliated graphene two-dimensional nanosheets with an average lateral size of about 200nm through 1h of 650W probe ultrasound and 2h of 11000rpm centrifugal purification.

[0064] Step 2: Prepare large-size Ti3C2T by HF etching x The two-dimensional nanosheets were then purified by 1 h of 650 W probe ultrasound and 0.5 h of 10,000 rpm centrifugation to obtain small-sized Ti3C2T with an average lateral size of about 200 nm. x Two-dimensional nanosheets.

[0065] Step 3: Using a 38 mm diameter filtration device, add 60 mg of small-sized electrochemically exfoliated graphene two-dimensional nanosheets or small-sized Ti3C2T x The suspension of two-dimensional nanosheets was vacuum filtered until the liquid disappeared and then immediately stopped, and the active material surface loading was 5.0 mg / cm 2 Small-sized electrochemically exfoliated graphene two-dimensional nanosheet hydrated films and small-sized Ti3C2T x Two-dimensional nanosheet hydrated films serve as the positive and negative electrodes of supercapacitors.

[0066] Step 4: Electrochemically exfoliate small-sized graphene two-dimensional nanosheets and hydrated thin films of small-sized Ti3C2T x The two-dimensional nanosheet hydrated film is separated by a diaphragm, and then the electrolyte is injected to assemble the supercapacitor device, and the open circuit potential of the positive and negative electrodes is adjusted to about -0.35 V. Among them, the diaphragm is a layer of glass fiber filter membrane, and the electrolyte is 3 mol / L H2SO4.

[0067] The performance of the supercapacitor was verified, and the test results showed that the device voltage could reach 1.8V and exhibited 0.27Wh / cm at a discharge rate of about 10C. 2 The energy density of the 2000C ultra-high rate is 0.10Wh / cm 2 The energy density is 10A / g, and the capacitance retention rate is greater than 95% after 10,000 charge and discharge cycles at a current density of 10A / g.

[0068] It can be seen that the supercapacitor device of the present invention is realized by selecting positive and negative electrode materials, matching the positive and negative electrode capacities and masses, adjusting the positive and negative electrode open circuit potentials, and constructing short lateral ion channels in the electrodes. It can meet the application needs of explosive energy storage and release scenarios, and is also a powerful substitute for current commercial organic supercapacitors at low rates.

[0069] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. A method for preparing an ultra-high rate, high energy density aqueous supercapacitor, characterized in that: The method comprises the following steps: Step 1, preparing small-sized graphene two-dimensional nanosheets; Step 2: Preparation of small size Ti3C2T x Two-dimensional nanosheets; Step 3: Preparation of small-sized graphene two-dimensional nanosheet hydrated films and small-sized Ti3C2T x Two-dimensional nanosheet hydrated film, the small-sized graphene two-dimensional nanosheet hydrated film is used as a positive electrode, the small-sized Ti3C2T x Two-dimensional nanosheet hydrated film as negative electrode; Step 4: Hydration of the small-sized graphene two-dimensional nanosheet film and the small-sized Ti3C2T x The two-dimensional nanosheet hydrated thin film is separated by a diaphragm, and then an electrolyte is injected to realize the assembly of the aqueous supercapacitor.

2. The method for preparing an ultra-high rate, high energy density aqueous supercapacitor according to claim 1, characterized in that: The step 1 also includes: Step 1.1, preparing large-sized graphene two-dimensional nanosheets; Step 1.2: Obtain small-sized graphene two-dimensional nanosheets through probe ultrasound and centrifugal purification.

3. The method for preparing an ultra-high rate, high energy density aqueous supercapacitor according to claim 2, characterized in that: In the step 1.1, the large-sized graphene two-dimensional nanosheets are large-sized reduced oxide graphene two-dimensional nanosheets or large-sized electrochemically exfoliated graphene two-dimensional nanosheets.

4. The method for preparing an ultra-high rate, high energy density aqueous supercapacitor according to claim 3, characterized in that: The method for preparing the large-sized reduced graphene oxide two-dimensional nanosheets comprises: oxidizing flake graphite using the Hummer's method to obtain large-sized graphene oxide two-dimensional nanosheets, and then reducing the flake graphite to obtain large-sized reduced graphene oxide two-dimensional nanosheets.

5. The method for preparing an ultra-high rate, high energy density aqueous supercapacitor according to claim 3, characterized in that: The preparation method of the large-sized electrochemically exfoliated graphene two-dimensional nanosheets comprises: using 0.1M (NH4)2SO4 aqueous solution as an electrolyte, using graphite paper and a platinum mesh as a positive electrode and a negative electrode respectively, and using a direct current power supply to apply a voltage of 10V to electrochemically exfoliate graphite to obtain large-sized electrochemically exfoliated graphene two-dimensional nanosheets.

6. The method for preparing an ultra-high rate, high energy density aqueous supercapacitor according to claim 1, characterized in that: The step 2 also includes: Step 2.1: Preparation of large-size Ti3C2T by LiF / HCl etching x Two-dimensional nanosheets; Step 2.2: Obtain small-sized Ti3C2T by probe ultrasonication and centrifugal purification x Two-dimensional nanosheets.

7. The method for preparing an ultra-high rate, high energy density aqueous supercapacitor according to claim 1, characterized in that: The step 3 further comprises: using a suction filtration device with a diameter of 38 mm, adding 60 mg of the small-sized graphene two-dimensional nanosheets or the small-sized Ti3C2T x The suspension of the two-dimensional nanosheets is vacuum filtered until the liquid disappears and then immediately stopped to obtain the small-sized graphene two-dimensional nanosheet hydrated film and the small-sized Ti3C2T x Two-dimensional nanosheet hydrated film, in which the nanoparticles are arranged parallel to the surface.

8. The method for preparing an ultra-high rate, high energy density aqueous supercapacitor according to claim 1, characterized in that: The diaphragm is a glass fiber filter membrane.

9. The method for preparing an ultra-high rate, high energy density aqueous supercapacitor according to claim 1, characterized in that: The electrolyte is H2SO4.

10. The method for preparing an ultra-high rate, high energy density aqueous supercapacitor according to claim 1, characterized in that: The open circuit potential of the positive electrode and the negative electrode is adjusted to -0.35V.

Citation Information

Patent Citations

  • Method for preparing large-size high-quality graphene with controllable number of layers

    CN104058396A

  • Preparation method and application of graphene oxide / MXene composite film

    CN110124529A

  • Method for preparing graphene titanium carbide cross-linked thin film material and application of graphene titanium carbide cross-linked thin film material in supercapacitor

    CN115763087A

  • Graphene-MXene composite film with multilayer sandwich structure

    CN116723686A

  • Preparation method of room-temperature plasma activated MXene electrode material and product and application of room-temperature plasma activated MXene electrode material

    CN117153568A